Network Governance in Integrated Maritime Transportation Development in Southwest Papua - Didik Iskandar; Muhammad Irvan Nur’ Iva; Muhammad Lutfi Siraj (CV. Era Digital Nusantara, 2026)
The development of integrated maritime transportation in Southwest Papua is essential for improving regional connectivity, reducing logistical barriers, and supporting equitable economic development across coastal and island communities. However, achieving an integrated transportation system remains challenging due to fragmented institutional responsibilities, limited coordination among stakeholders, and differences in organizational priorities. This study explores how network governance contributes to the development of integrated maritime transportation in Southwest Papua. A qualitative case study approach was employed, using in-depth interviews, field observations, and document analysis to collect data from government agencies, port authorities, transportation operators, local communities, and other relevant stakeholders. The data were analyzed through an interactive qualitative process involving data reduction, data display, and conclusion drawing. The findings show that collaboration among organizations has been established, but its effectiveness is constrained by uneven levels of trust, varying degrees of stakeholder participation, limited agreement on shared objectives, and insufficient collective capacity to coordinate inter-organizational activities. These conditions reduce the effectiveness of collaborative governance and hinder the integration of maritime transportation services. Strengthening mutual trust, encouraging broader stakeholder participation, promoting shared goals, and enhancing institutional capacity are therefore critical to building an integrated, adaptive, and sustainable maritime transportation system capable of supporting long-term regional development in Southwest Papua.